Should I Leave or Not? The Role of LMX and Organizational Climate in Organizational Citizenship Behavior and Turnover Relationship (Journal of Organizational Psychology, 2017)
This study attempts to investigate the complex nature of the relationship between organizational citizenship behavior and turnover intentions. We argue that leader member exchange and organizational climate will moderate the relationship between organizational citizenship behavior and turnover intentions. The results of hierarchical regression analysis conducted on the data obtained from 216 employees working in the retail industry provide support to the hypothesized relationships. Implications for management practice and future research directions are discussed.
Keywords: Organizational Psychology; LMX; Management